2020
DOI: 10.3390/insects11020129
|View full text |Cite
|
Sign up to set email alerts
|

New Tools for Conservation Biological Control: Testing Ant-Attracting Artificial Nectaries to Employ Ants as Plant Defenders

Abstract: Knowledge of the role of ants in many agroecosystems is relatively scarce, and in temperate regions the possibility to exploit ants as biocontrol agents for crop protection is still largely unexplored. Drawing inspiration from mutualistic ant-plant relationships mediated by extrafloral nectaries (EFNs), we tested the use of artificial nectaries (ANs) in order to increase ant activity on pear trees and to evaluate the effects on the arthropods, plant health and fruit production. While EFNs secrete a complex sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 107 publications
2
38
0
Order By: Relevance
“…However, under similar conditions C. scutellaris (another ant common in agroecosystems) had a greater impact (Castracani et al., 2017). This points out the need to consider the diversity in the behaviour and ecological roles of the various ant species as natural pest managers in agroecosystems (Hölldobler & Wilson, 1990; Way & Khoo, 1992; Maňák et al., 2013; Schifani et al., 2020). Ant diversity and ecology, different feeding habits, behavioural ecology, and impact on the dynamics of species assemblages and community structure, as well as specific climate and environmental factors, suggest the importance of considering both single species and community effect on herbivores in agroecosystems to better plan programs of conservation biological control and IPM involving ants (Gibb et al., 2017; Arnan et al., 2018; Castracani et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under similar conditions C. scutellaris (another ant common in agroecosystems) had a greater impact (Castracani et al., 2017). This points out the need to consider the diversity in the behaviour and ecological roles of the various ant species as natural pest managers in agroecosystems (Hölldobler & Wilson, 1990; Way & Khoo, 1992; Maňák et al., 2013; Schifani et al., 2020). Ant diversity and ecology, different feeding habits, behavioural ecology, and impact on the dynamics of species assemblages and community structure, as well as specific climate and environmental factors, suggest the importance of considering both single species and community effect on herbivores in agroecosystems to better plan programs of conservation biological control and IPM involving ants (Gibb et al., 2017; Arnan et al., 2018; Castracani et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among the various trophic roles, they are also predators of pest species (Cerdá & Dejean, 2011). This may represent an important service for plants hosting ants, for those that are more or less routinely visited by ants, or that are surrounded by ant colonies (Campolo et al., 2015; Giannetti et al., 2019; Schifani et al., 2020). Several ant species are robust predators or exhibit very aggressive reactions against other animals including herbivores (Hölldobler & Wilson, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Later, the trees were isolated with adhesive strips (glue bands, Stocker art. 45118) at the base of the trunk to prevent any successive ant colonization [ 4 , 37 ]. The galls were left on the trees for one year before being retrieved (from September 2016 to October 2017, coinciding with the period of Crematogaster scutellaris (Olivier, 1792) nuptial flights and foundation of new colonies [ 38 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, several studies have shown reduced disease incidence on antpatrolled plants compared to plants without ants. These include a few studies on agricultural crops, such as apple, pear and mango, experiencing reduced scab symptoms Peng & Christian, 2005Schifani et al, 2020) as well as natural ant-plant symbioses, where plants are relieved from various plant diseases. A meta-analysis of such studies showed that ants may be as detrimental to plant pathogens as they are to arthropod herbivores .…”
Section: Using Live Antsmentioning
confidence: 99%
“…Multiple studies show that the presence of ants can lead to reduced plant disease incidence. A recent review study identified 13 ant species that were able to control 14 fungal, oomycete and bacterial plant pathogens on 12 different plant species , and two subsequent studies showed reduced incidence of scab and fruit rot on ant associated apple and pear trees compared to control trees without ants Schifani et al, 2020). A further recent study showed that oak seedlings inhabited by ants showed reduced incidence of leaf fungal attacks compared to ant-free control seedlings (Giannetti et al, 2019).…”
mentioning
confidence: 99%